Comparative heat transfer analysis in different mini-channel heat sinks - Afzal, Asif; Samee, Mohammad; Khan, Sher Afghan (Institute of Institutional Industrial Research, 2017)
The present experimental investigation is mainly focused on thermal analysis of different geometry of minichannel heat sink subjected to flow of water as a fluid under steady state forced convection flow condition. The objective is to determine the effect of flow rate on heat transfer and fluid flow characteristics of rectangular, circular, trapezoidal and square shape mini-channels with hydraulic diameter of 2 mm and length 250 mm each with an array of ten numbers of channels. From the present experimental study it is observed that the flow rate has great impact on the heat transfer characteristics. The geometry of mini-channel also plays a vital role on heat transfer and fluid flow behavior. It is also observed that pumping power required for circular geometry of mini-channel is maximum compared to other type of mini-channels and it is minimum for rectangular mini-channels.